2011
DOI: 10.3389/fnins.2011.00045
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Integration of Newborn Neurons after Neonatal Insults

Abstract: The production and integration of adult-generated neurons in the dentate gyrus is dramatically perturbed by a variety of pathological insults, including repetitive seizures and hypoxia/ischemia. Less is known about how insults affect early postnatal neurogenesis, during the developmental period when the majority of dentate neurons are produced. Here we tested how single episodes of hypoxia or chemically induced seizure activity in postnatal day 10 mice alter granule cell production and integration. Although ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…It was believed that neural activity in the DG might affect the development of granule cell by both cell-autonomous and non-cell-autonomous mechanisms (Tozuka et al, 2005;Ge et al, 2006;Ma et al, 2009). In support of this idea, the enhanced dendritic structures in the newborn DGCs, one week after neonatal hypoxia, were associated with enhanced GABA-mediated synaptic inputs (Shapiro et al, 2005;Shapiro and Ribak, 2006;Walter et al, 2007;Pugh et al, 2011).…”
Section: Hypoxia-induced Neonatal Seizures Promoted Abnormal Neurogenmentioning
confidence: 77%
See 2 more Smart Citations
“…It was believed that neural activity in the DG might affect the development of granule cell by both cell-autonomous and non-cell-autonomous mechanisms (Tozuka et al, 2005;Ge et al, 2006;Ma et al, 2009). In support of this idea, the enhanced dendritic structures in the newborn DGCs, one week after neonatal hypoxia, were associated with enhanced GABA-mediated synaptic inputs (Shapiro et al, 2005;Shapiro and Ribak, 2006;Walter et al, 2007;Pugh et al, 2011).…”
Section: Hypoxia-induced Neonatal Seizures Promoted Abnormal Neurogenmentioning
confidence: 77%
“…Recently, Pugh et al investigated the effects of neonatal seizures induced by hypoxia with P10 mice on the dendritic morphology of newborn DGCs and found that hypoxia-induced seizures increased the total dendritic length of newborn DGCs by 15% one week after seizure induction. However, the total dendritic length of newborn DGCs significantly decreased 2 month after seizure induction (Pugh et al, 2011). These results suggested that neonatal seizures induced by global hypoxia might distinctively impact short-and long-term consequences of dendritic development of newborn DGCs.…”
Section: Hypoxia-induced Neonatal Seizures Promoted Abnormal Neurogenmentioning
confidence: 84%
See 1 more Smart Citation
“…MicroBrightField, Williston, VA) (Pugh et al 2011). Cells with obvious truncation were excluded from analysis.…”
Section: Methodsmentioning
confidence: 99%
“…One way in which this can occur is through altered neuron morphology and synaptogenesis, both of which are seen after neonatal seizures in the rat (Holmes et al, 2002; Pugh et al, 2011). As a fundamental developmental process, synaptogenesis is regulated in a sexually dimorphic manner under the influence of steroid hormones, as has been demonstrated in several areas of the brain in the neonatal rat.…”
Section: Perinatal Sex Differences In Mechanisms That Promote Long-tementioning
confidence: 99%